Identification of Taekwondo Athlete Talent by Using Analytic Hierarchy Process (AHP) Softwear - Rini Andriani; Agus Rusdiana (Jurnal Pendidikan Jasmani (JPJ), 2023)
AHP is designed to solve complex problems in hierarchies, unclear structures, uncertain opinions of a decision, many decision makers, and inaccuracies in existing data. This study aims to determine the criteria and sub-criteria in identifying the talent of taekwondo athletes aged 12 to 14 years. The data collected and analyzed using the Analytic Hierarchy Process (AHP) with the expert choice application. The method used in this research is a combination method (mixed-methods research) by conducting a literature review and providing questionnaires to 30 taekwondo experts in West Java. Of the thirteen sub-criteria, ten sub-criteria were the highest with data analysis using AHP. The ten sub criteria include mesomorph, endomorph, height, ectomorph, V02Max, Body Mass Index, weight, agility, speed and leg length.